Redescription of Liolaemus robertmertensi, Hellmich 1964 (Iguania: Liolaemidae) with description of a new species - Fernandez, Maria Gimena (2021)
We redescribe Liolaemus robertmertensi and describe a new species of Liolaemus, the secondmost speciose lizard genus. These species belong to the L. robertmertensi group of the subgenusLiolaemus sensu stricto. In recent years, some newly identified populations were assignedto Liolaemus robertmertensi. We applied an integrative approach using morphological andphylogenetic evidence to determine the relationships among these populations and found oneto belong to a new species described here. We performed statistical analyses to differentiate L.robertmertensi and the new species from other species of the alticolor-bibronii group. The newspecies shows a set of character states that allows it to be distinguished from L. robertmertensiand from all other species of Liolaemus. Despite the description of this new species, the taxonomicstatus of many populations still remain unknown.